PENERAPAN BALANCE SCORE CARD (BSC) SEBAGAI ALAT PENILAIAN KINERJA PT SAMATOR GAS INDONESIA - Rudi Pratono (UMSurabaya Publishing, 2011)
Successful implementation of the Balanced Scorecard is largely determined by the process of preparing/developing the Balanced Scorecard itself. Balanced Scorecard is a new framework that integrates the various measures derived from the company's strategy. Preparation of the Balanced Scorecard PT Samator Gas Industry based on 2011 Business Plan. Information on the Balanced Scorecard development has not been adequately communicated to all levels of the organization. Application of Balanced Scorecard in the Gas Industry PT Samator not preceded by a preparation that support the implementation of this system. These programs include participation and socialization. Management company to change the view on the concept of Balanced Scorecard. Measures in the scorecard is not simply a static model can not be changed. The drafting team to integrate the Balanced Scorecard strategy Samator PT Gas Industry as a whole into the scorecard PT Samator Gas Industry. Keywords: Balance Score Card, Performance.